Implementasi Capaian Program Universal Health Coverage di Indonesia: Narrative Review - Nirmalasari, Melisa Yuni; Idris, Haerawati; Flora, Rostika (Health Information : Jurnal Penelitian, 2023)
National Health Insurance is one of the government's programs as an effort to achieve Universal Health Coverage (UHC) which has been declared in the Sustainable Development Goals (SDGs). There are several regions in Indonesia that have received the UHC designation with achievements of more than 95%. The aim of this research is to describe the implementation of UHC achievements in Indonesia. The method used in this research is a Literature Review with a Narrative Literature Review approach. The articles used are articles with a publication time span of 5 years from 2018-2023 from several databases such as Google Scholar and PubMed. The results of this research show that UHC achievements in Indonesia are still faced with challenges in covering informal sector participation and there are several strategies and policies issued by Regional governments in achieving UHC in their regions including the role and commitment of actors, cross-sector coordination, efforts to expand JKN membership coverage, providing sufficient budgets, improving the quality of health services and capacity of health human resources, creating innovative programs to achieve UHC. In addition, Indonesia applies indicators to measure UHC achievements by calculating the essential health service coverage index and financial protection against health costs. In conclusion, the implementation of the UHC program achievements in Indonesia is still experiencing various challenges so appropriate strategies and policies are needed.